2014
DOI: 10.1155/2014/945814
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Nrf2‐Mediated Phase II Enzymes Critical for Protection of Tao Hong Si Wu Decoction against Oxygen Glucose Deprivation Injury in PC12 Cells

Abstract: Chinese herbal medicine formula Tao Hong Si Wu decoction (THSWD) is traditionally used in China for cerebrovascular diseases. However, the molecular mechanisms of THSWD associated with the cerebral ischemia reperfusion injury are largely unknown. The current study applied the two-dimensional gel electrophoresis-based proteomics to investigate the different protein profiles in PC12 cells with and without the treatment of THSWD. Twenty-six proteins affected by THSWD were identified by MALDI-TOF mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…These six proteins are under Nrf2 regulation at the transcription level in a dose‐dependent manner. Importantly, the protection of THSWD against OGD/R‐induced cell death was significantly attenuated by ARE decoy oligonucleotides, suggesting that Nrf2 activation has a role in THSWD neuroprotection (Qi et al, ).…”
Section: Strokesmentioning
confidence: 99%
“…These six proteins are under Nrf2 regulation at the transcription level in a dose‐dependent manner. Importantly, the protection of THSWD against OGD/R‐induced cell death was significantly attenuated by ARE decoy oligonucleotides, suggesting that Nrf2 activation has a role in THSWD neuroprotection (Qi et al, ).…”
Section: Strokesmentioning
confidence: 99%
“…Compared to BHD, THSWD was also used for treating cerebrovascular diseases with different molecular mechanism. Qi et al [23] found that THSWD could change the proteome of rat pheochromocytoma cells, hence it mediated protective effect on cerebral IR injury. They speculated that the protection effect of THSWD might regulated partly by six of Nrf2-driven phase II enzymes, which were validated in transcription level by real-time PCR.…”
Section: Differential Proteomics For Exploring the Action Mechanisms mentioning
confidence: 99%
“…Fan et al [35] determined the protein expression profiles of rat mesenchymal stem cells and cardiomyocyte-like cells by the 2DGE technique and found that the Shuanglong formula could induce mesenchymal stem cells to transform into cardiomyocyte-like cells. In the same vein, the determination of protein expression profiles was conducted in research on the effect of the Fuzheng Huayu formula [36] and Yinchenhao decoction [37] on the proteome of fibrotic livers, as well as the effects of the ZiBu PiYin recipe [38] and Tianqi Jiangtang capsule on diabetes, of Yuanshi Shengmai Chenggu tablets on avascular osteonecrosis of the femoral head [39], of Jie-Geng-Tang on lipopolysaccharide-induced acute lung injury in mice [40], and of the Tao Hong Si Wu decoction against ischemia reperfusion injury [41].…”
Section: Application Of Proteomics In Chf Researchmentioning
confidence: 99%